Protein Tungau Sarcoptes Scabiei Sebagai Penyebab Stres Oksidatif Pada Kulit yang Terinvestasi Parasit - Trasia, Reqgi First; Mustofa, Samsul; Purwaningsih, Endang; Herlinawati, Sri Wahyu (Universitas Pekalongan, 2025)
S. scabiei infestation triggers many reactions including allergic reactions, inflammation, innate immune reactions, and activation of immune components in the skin accompanied by oxidative stress stages. This article aims to examine the genetic characterization of S. scabiei and gain a better understanding of host-parasite interactions with particular emphasis on skin oxidative stress parameters such as oxidant/antioxidant balance, stress parameters, and immune responses. This article is compiled as a systematic review by examining a number of relevant publications. Based on this search, it was found that to determine the effect of S. scabiei infestation on the oxidant/antioxidant balance in serum, oxidative stress markers such as total antioxidant activity (T-AOC), total nitric oxide concentration (TNO), lipid peroxide levels, and malonyldialdehyde (MDA) were used, as well as antioxidant enzyme levels; superoxide dismutase (SOD), glutathione-S-transferase (GSH) and catalase. Oxidative stress has been shown to be involved in the pathogenesis of several parasitic infectious diseases including scabies. Host cell metabolism produces ROS and RNS. At low to moderate levels, they are involved in several physiological functions including cell signaling and immune function. Conversely, at high levels, they cause damage to molecules including lipids, proteins, lipoproteins, and nucleic acids starting from a chain reaction of free radical formation leading to a condition known as oxidative stress. This article recommends a meta-analysis study to obtain more in-depth review results for further research..